The Effectiveness Test Of Natural Hair Growth Tonic: Avemor (Aloe Vera And Moringa Oleifera) For Thickening Hair And Anti-Licknes - Iin Suhesti; Annisa Diyan Meitasari; Nila Efa Sulistiana; Dinar Azizah (CV. Inara, 2024)
Avemor (Aloe vera and Moringa oleifera) is a natural hair growth tonic manufactured with a combination of aloe vera gel and dried moringa leaf extract as its active ingredients. Aloe vera includes a variety of vitamins and minerals, including vitamins A and C, amino acids, copper, inositol, and others. The extract from moringa leaves also includes tanins, vital amino acids, vitamin C, vitamin E, and other nutrients. One of the products with 2% minoxidil is employed as a positive control. Several hair diseases are treated off-label with the powerful arteriol vasoconstrictor minoxidil, which can also promote hair growth. In order to determine the effectiveness of Natural Hair Growth Tonic, tests were done on male New Zealand white rabbit hair. Avemor (Aloe vera and Moringa oleifera) is one of the products containing 2% minoxidil, with variations in the content of dried moringa leaf extracts of 2%, 4%, and 6% in comparison to the positive control. On the backs of five rabbits, six test regions were created, and each area received a different treatment every day using a sample volume of 0.5 ml. Results of the Natural Hair Growth Tonic's physical evaluation: Avemor (Aloe vera and Moringa oleifera) has a liquid shape, a distinct aroma, a pH of 6, and is homogeneous with the yellow-golden color of the formulae 1 and 2 as well as the golden brown in the formula 3. It also varies in the concentration of the dried moringa leaf extracts. Formula 4 (negative control) has the appearance of a liquid, is dazzling white in color, and emits a distinct odor. Additionally, formula 5 (positive control) has a liquid-like consistency, a vivid yellowish color, and a distinguishable scent. The average reserve viscosity for formula 1 was 2.96 ± 0.14 cPs, for formula 2 it was 2.99 ± 0.10 cPs, and for formula 3 it was 4.05 ± 0.07 cPs. Formula 4 (negative control) had a value 2.96 ± 0.10 cPs, and formula 5 (positive control) had a value of 1.82 ± 0.03 cPs. The average result of rabbit hair growth on the seventh day for treatment 1 is 0.22 ± 0.17 cm, treatment 2 is 0.30 ± 0.23 cm, treatment 3 is 0.42 ± 0.42 cm, treatment 4 is 0.58 ± 0.47 cm, treatment 5 is 0.68 ± 0.36 cm, and treatment 6 is 0.90 ± 0.42 cm. On the 14th day of treatment 1, the average result of rabbit hair growth was 0.43 ± 0.06 cm; on the same day, treatment 2, 0.27± 0.18 cm; on the same day, treatment 3, 0.42 ± 0.33 cm; on the same day, treatment 4, 0.77 ± 0.22 cm; on the same day, treatment 5, 0.28 ± 0.24 cm; and on the same day, treatment 6, 0.43 ± 0.38 cm. The average length of rabbit hair on the 21st day for treatment 1 was 0.43 ± 0.26 cm, for treatment 2 was 0.73 ± 0.19 cm, for treatment 3 was 0.32 ± 0.23 cm, for treatment 4 was 0.48 ± 0.31 cm, for treatment 5 was 0.13 ± 0.17 cm, and for treatment 6 was 0,43 ± 0.30 cm.